2018
DOI: 10.1016/j.aquatox.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of cadmium, zinc, arsenic and chromium on olfactory-mediated neurobehavior and gene expression in larval zebrafish (Danio rerio)

Abstract: Studies have shown that olfactory-mediated behaviors that are critical to survival can be disrupted by exposure to certain metals. Aquatic Superfund sites often contain elevated levels of various metals, yet few have been characterized for their potential to cause olfactory toxicity. A larval zebrafish behavioral assay was developed to characterize concentration-response curves for zinc (Zn), hexavalent chromium (Cr), and arsenate (As) olfaction inhibition. Cadmium (Cd), an established olfactory toxicant, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Previous experiments have shown that cadmium enters other cell types through zinc transporters (Dalton et al, 2005;Fujishiro et al, 2009), and that zinc can block cadmium uptake (Barbier et al, 2004;Girijashanker et al, 2008). Zinc has also previously been shown to protect against impaired behavioral responses to odorants caused by cadmium in larval zebrafish (Heffern et al, 2018) and to protect against impaired auditory responses caused by cadmium in rats (Agirdir et al, 2002). To test whether zinc could likewise protect against cadmiuminduced hair cell death in zebrafish, we co-treated fish with 30 µM of cadmium chloride and varying doses of zinc sulfate, based on doses that had previously been shown to protect against cadmium-induced defects in olfactory behavior in larval zebrafish (Heffern et al, 2018), with and without a 1-h zinc sulfate pretreatment.…”
Section: Zinc and Copper Cotreatment Do Not Protect Hair Cells From Cmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous experiments have shown that cadmium enters other cell types through zinc transporters (Dalton et al, 2005;Fujishiro et al, 2009), and that zinc can block cadmium uptake (Barbier et al, 2004;Girijashanker et al, 2008). Zinc has also previously been shown to protect against impaired behavioral responses to odorants caused by cadmium in larval zebrafish (Heffern et al, 2018) and to protect against impaired auditory responses caused by cadmium in rats (Agirdir et al, 2002). To test whether zinc could likewise protect against cadmiuminduced hair cell death in zebrafish, we co-treated fish with 30 µM of cadmium chloride and varying doses of zinc sulfate, based on doses that had previously been shown to protect against cadmium-induced defects in olfactory behavior in larval zebrafish (Heffern et al, 2018), with and without a 1-h zinc sulfate pretreatment.…”
Section: Zinc and Copper Cotreatment Do Not Protect Hair Cells From Cmentioning
confidence: 98%
“…Zinc has also previously been shown to protect against impaired behavioral responses to odorants caused by cadmium in larval zebrafish (Heffern et al, 2018) and to protect against impaired auditory responses caused by cadmium in rats (Agirdir et al, 2002). To test whether zinc could likewise protect against cadmiuminduced hair cell death in zebrafish, we co-treated fish with 30 µM of cadmium chloride and varying doses of zinc sulfate, based on doses that had previously been shown to protect against cadmium-induced defects in olfactory behavior in larval zebrafish (Heffern et al, 2018), with and without a 1-h zinc sulfate pretreatment. We found no significant reduction in hair cell death in response to cotreatment alone ( Figure 4A), and only a slight reduction at the highest zinc sulfate dose tested 1,364 µM, which is equivalent to 88 µg/L zinc, in response to the 1-h pretreatment combined with cotreatment ( Figure 4B).…”
Section: Zinc and Copper Cotreatment Do Not Protect Hair Cells From Cmentioning
confidence: 99%
“…Zinc has also previously been shown to protect against impaired behavioral responses 191 to odorants caused by cadmium in larval zebrafish (Heffern et al, 2018) and to protect 192 against impaired auditory responses caused by cadmium in rats (Agirdir et al, 2002). 193…”
Section: Zinc and Copper Cotreatment Do Not Protect Hair Cells From Cmentioning
confidence: 99%
“…To test whether zinc could likewise protect against cadmium-induced hair cell death in 194 zebrafish, we co-treated fish with 30 µM of cadmium and varying doses of zinc, based 195 on doses that had previously been shown to protect against cadmium-induced defects 196 in olfactory behavior in larval zebrafish (Heffern et al, 2018), with and without a one-197 hour zinc pretreatment. We found no significant reduction in hair cell death in response 198 to cotreatment alone ( Figure 4A), and only a slight reduction at the highest zinc dose, 199 88 µg/L, in response to the one-hour pretreatment combined with cotreatment ( Figure 200 4B).…”
Section: Zinc and Copper Cotreatment Do Not Protect Hair Cells From Cmentioning
confidence: 99%
See 1 more Smart Citation